A [Gamma]-structure on Lagrangian Grassmannians - Albers, Peter; Frauenfelder, Urs; Solomon, Jake P. (Arxiv, 2013)
For n odd the Lagrangian Grassmannian of R^{2n} is a Γ-manifold.
Im Titel wird "Gamma" als griechischer Buchstabe dargestellt
Gesehen am 18.02.2019